Permasalahan Kesulitan Akademik Peserta Didik Di Sekolah Dasar - Ramadhan Putra Pamungkas; Gracia Putri Natalia; Mella Tia Tristanti; Maharani Dwi Wahyu Nindiasari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research aims to identify the obstacles faced by students in the learning process and how to overcome them. The method used is library research or library research. Learning difficulties are conditions in which students cannot achieve set learning goals, caused by gaps between intellectual and academic abilities, such as dyslexia, dyscalculia, and dysgraphia. This gap is a complex problem at the elementary school level that requires short and long term attention. This research identifies factors that cause learning difficulties, including a monotonous training system, lack of family support, and students' inability to learn. Data was collected through interviews with teachers, student surveys, and classroom observations. The research results show that students have difficulty learning basic material, especially in mathematics and language. This has a negative impact on their motivation and self-confidence. A holistic intervention approach, involving teachers, parents and the school, is considered an effective solution to help students overcome learning difficulties. This research also provides recommendations about strategies that can be implemented to help students overcome their academic problems. Appropriate interventions can improve learning outcomes and student well-being at school.